C3 and C4 complement levels in AQP4-IgG-positive NMOSD and in MOGAD - Pache, Florence; Ringelstein, Marius; Aktas, Orhan; Kleiter, Ingo; Jarius, Sven; Siebert, Nadja; Bellmann-Strobl, Judith; Paul, Friedemann; Ruprecht, Klemens (Journal of neuroimmunology, 2021)
While complement-dependent cytotoxicity (CDC) is a known effector mechanism in aquaporin-4-immunoglobulin (Ig)G-positive (AQP4-IgG+) neuromyelitis optica spectrum disorder (NMOSD), the role of CDC in myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is less clear. We determined complement C3 and C4 plasma concentrations in patients with clinically stable AQP4-IgG+ NMOSD (n = 16), MOGAD (n = 15), early multiple sclerosis (MS, n = 19) and in healthy controls (HC, n = 18). C4 was lower in AQP4-IgG+ NMOSD than in MOGAD, MS and HC (p < 0.05, pairwise comparisons). C3 was lower in AQP4-IgG+ NMOSD than in MS (p = 0.034). These findings suggest subtle complement consumption in clinically stable AQP4-IgG+ NMOSD, but not in MOGAD.
Gesehen am 15.01.2022